2013
DOI: 10.1016/j.jtcvs.2012.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and echocardiographic outcomes after surgery for severe isolated tricuspid regurgitation

Abstract: In the present cohort, preoperative anemia, renal/hepatic dysfunction, right ventricular dilatation, and significant postoperative tricuspid regurgitation were associated with poor outcomes. Timely surgery is advisable in patients with severe isolated tricuspid regurgitation before the development of anemia, organ dysfunction, or right ventricular dilatation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
55
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(62 citation statements)
references
References 17 publications
5
55
0
2
Order By: Relevance
“…We characterized and compared structural heart changes in no/trace TR, mild TR, and moderate/severe TR using cardiac CTA for enhanced cardiac structural measurement. 8,18,[27][28][29][30] Tricuspid Regurgitation: Cardiac Structural Changes Across Tricuspid Regurgitation Severity…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We characterized and compared structural heart changes in no/trace TR, mild TR, and moderate/severe TR using cardiac CTA for enhanced cardiac structural measurement. 8,18,[27][28][29][30] Tricuspid Regurgitation: Cardiac Structural Changes Across Tricuspid Regurgitation Severity…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] The timing of tricuspid valve surgery is important because patients with TR have anemia, organ dysfunction, and right ventricular (RV) dilatation, which also are associated with poor surgical outcomes. 8 Structural heart changes in severe TR are well described and include tricuspid annular dilation and RV and right atrial (RA) enlargement. Tricuspid annuloplasty has favorable effects on right heart structure, [9][10][11] and early intervention can prevent right heart dilation and TR progression.…”
mentioning
confidence: 99%
“…17 In addition, these data are largely derived from the cohorts of patients who underwent the tricuspid valve surgery. [18][19][20][21][22] There are a few reports on the natural history of isolated TR. 4,5 Topilsky et al reported that isolated TR (functional TR with no left-sided valvular disease, no decreased LVEF, and no pulmonary hypertension) significantly affected survival.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al recently reported that there was no meaningful difference between TVR and TVr as a treatment for isolated severe TR. 13 This suggests that the clinical outcomes of tricuspid valve surgery are mainly related to preoperative characteristics, not to the type of surgery itself. To date, some studies have already drawn the conclusion that there appears to be no significant difference in clinical outcomes between the 2 approaches, 4,7,8 but the study period ranged from the 1970 s, or the operative mortality was high from the viewpoint of current standard practice.…”
Section: Discussionmentioning
confidence: 99%